(untitled) (Experimental biology, 2015)
Simple and clear look at what the cause of obesity is an imbalance between calorie intake and their waste, unfortunately,has not justified itself in practice. This is due largely to the fact that the calories of food before they are used for energy needs are included firstly in the structural component and the organism depot. Although energy costs of protein synthesis are large, nobody holds their account, so there is constantly a discrepancy between calorie intake and their waste. In connection with this important aspect of diabetes and obesity development is to reduce energy consumption for protein synthesis as a result of the substrate deficiency, protein-synthesizing apparatus destruction and the reduction of anabolic stimulus.